Uncommon Oral Manifestations and Growth Failure in A Pediatric Multisystem Langerhans Cell Histiocytosis: A Case Report - Janardhan, Kavya; Khan, Azmathulla; Das Mazumder, Mithila; Pushpa, Manjushree; Swaraj, SL Akhila; S Asangi, Santoshkumar (Journal of Neonatal Surgery, 2025)
Langerhans cell histiocytosis (LCH) is a rare condition characterized by the clonal proliferation of Langerhans cells, leading to varying degrees of organ dysfunction. This report presents a challenging case of multisystem LCH in a 1-year-8-month-old female, exhibiting symptoms like gingival hypertrophy, cutaneous lesions, and failure to thrive. Diagnosis was confirmed by histopathology and immunohistochemistry, which revealed CD1a-positive Langerhans cells. The patient underwent chemotherapy, achieving significant clinical improvement. This report emphasizes the need for vigilance when evaluating pediatric patients with nonspecific symptoms and the importance of a multidisciplinary approach in diagnosing and managing this rare disorder.